Muhammad Abduh dan Pemikiran Pembaharuannya - Iskandar Usman (Jurnal Pemikiran Islam, 2022)
The fall of Egypt, which was one of the centers of Islamic culture and civilization, into the hands of the West in 1798 CE, inspired the Islamic world of its weaknesses and made Muslims aware that in the West a new higher civilization had arisen and was a threat to Islam. The kings and leaders of Islam began to think about how to improve the quality and strength of Muslims again. So were born the ideas of renewal in Islam, which began in Egypt with one of its famous characters, Muhammad Abduh. This study aims to examine how Muhammad's reformed thoughts and the influence of his reformed thoughts on the Islamic world. This research uses a qualitative research method with a literature review technique and uses library study data. According to Abduh, the reasons for the weakness of Muslims are mental poverty and the incorrect direction of thinking, but the main reasons are stupidity and misunderstanding of Islam and life. And to improve the situation of the people as a whole, it must be restored to the soul of togetherness, nationality, Islam, and humanity in general with the development of religion and religious teaching in Education from the basic level. Muhammad Abduh's reform thinking includes four core aspects: politics and nationality, social, belief, education and general teaching. Abduh's thoughts influence in Egypt has given birth to modern scholars, religious writers, political leaders, and Arab litterateur. His opinions and teachings have influenced the Islamic world through his own essays and through the writings of his students.AbstrakJatuhnya Mesir yang merupakan salah satu pusat kebudayaan dan peradaban Islam ke tangan Barat pada 1798 M, menginsafkan dunia Islam akan kelemahannya dan menyadarkan umat Islam bahwa di Barat telah timbul peradaban baru yang lebih tinggi dan merupakan ancaman bagi Islam. Raja-raja dan pemuka-pemuka Islam mulai memikirkan bagaimana meningkatkan mutu dan kekuatan umat Islam kembali. Maka lahirlah ide-ide pembaharuan  dalam Islam, yang dimulai di Mesir dengan salah satu tokohnya yang terkenal, Muhammad Abduh. Penelitian ini bertujuan untuk mengkaji bagaimana pemikiran-pemikiran pembaharuan Muhammad dan bagaimana pengaruh pemikiran-pemikiran pembaharuannya bagi dunia Islam. Penelitian ini menggunakan metode penelitian kualitatif dengan teknik literature review dan menggunakan data studi kepustakaan. Menurut Abduh, sebab-sebab kelemahan umat Islam adalah kemiskinan jiwa dan salahnya arah berpikir, namun sebab utamanya adalah kebodohan dan pemahaman yang salah terhadap Islam dan kehidupan. Dan untuk memperbaiki keadaan umat secara menyeluruh mesti dikembalikan jiwa kebersamaan, kebangsaan, Islam, dan kemanusiaan secara umum dengan pengembangan agama dan pengajaran agama pada Pendidikan sejak dari tingkat dasar. Pemikiran pembaharuan Muhammad Abduh mencakup empat segi inti: politik dan kebangsaan, sosial, keyakinan, Pendidikan dan pengajaran umum. Pengaruh pemikiran Abduh di Mesir telah melahirkan ulama-ulama modern, pengarang-pengarang dalam bidang agama, pemimpin politik, dan sastrawan-sastrawan Arab. Pendapat-pendapat dan ajarannya telah mempengaruhi dunia Islam melalui karangan-karangannya sendiri dan melalui tulisan-tulisan murid-muridnya.